Análisis e implementación de protocolos de enrutamiento en una red ad hoc aérea (fanet) para la telegestión de uavs - Carchi Curimilma, Jhonny Medardo (2022)
With the technological advances, multiple UAV systems capable of performing missions together are being developed to improve the efficiency of single UAV systems. This new operation design requires the development of new connection technologies for networks between drones and the ground station. The drone-to-drone network is an airborne Ad Hoc network and is a type of network derived from MANET. This new kind of network presents some drawbacks that need to be addressed before deployment for the network to provide stability and reliability in the connections. In this degree work, Network Simulator version 3 (Ns-3) software is used to simulate a FANET network to analyze the efficiency of routing protocols for mobile Ad Hoc networks, modifying the density of nodes and the simulation area. The metrics that determine the efficiency of the network are end-to-end delay, Throughput, and PDR (Packet Delivery Ratio). In implementing the physical FANET network, the Optimized Link State Routing (OLSR) routing protocol was applied since it offers a better performance in the network according to the results obtained.